Ayashimon. 1, I'll play with you, punk - Kaku, Yuji; Kaku, Yuji (Shonen Jump manga., 2023)
"When the Enma Syndicate's chairman dies, Japan's supernatural underworld is turned on its head, leaving gangs of ayashimon poised on the brink of war. Urara, the late chairman's daughter, has plans to come out on top, and she's found an unlikely ally to help make it happen--Maruo, a human who dreams of being a manga hero. Maruo always wanted to be like the characters in his favorite manga. Unfortunately, his training efforts have paid off a little too well. Now he breaks everything he touches, can't find a job, and wins every fight too easily. However, when he encounters a girl being pursued by a group of thugs who turn out to actually be monstrous ayashimon in disguise, it seems like his real-life manga story is about to begin!"--back cover.